Sustainability-Oriented Employee Mindsets as a Foundation for Environmental Health in the Palm Oil Sector - Muhammad Reza Aulia; Zulkarnain Lubis; Vivi Gusrini Rahmadani; Darmansyah Siregar; Mehaga Bastanta Sinulingga; Fantashir Awwal Fuqara; Utari Azrani; Cut Salsabila (Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores employee mindsets and their influence on sustainable agriculture within PTPN III (Persero), a state-owned enterprise in Indonesia’s palm oil sector. Using a qualitative case study design, thirty employees from field, supervisory, and administrative levels participated in semi-structured interviews conducted between January and June 2025. Thematic analysis identified six dominant mindsets: profit-oriented, compliance, growth, innovation, collaborative, and infinite. These represent a continuum from short-term productivity and regulatory adherence to long-term, visionary, and intergenerational commitments to sustainability. The analysis further revealed six traits influencing sustainability behavior: environmental awareness, social responsibility, ethical consciousness, innovation orientation, collaborative spirit, and advancement drive. Employees with higher levels of these traits actively engaged in environmentally responsible practices, while those with lower awareness demonstrated compliance-based behavior. The findings suggest that a sustainability-oriented mindset, characterized by long-term vision, accountability to nature and society, and adaptability to global challenges, is essential for advancing sustainable agriculture in PTPN III. Theoretically, this study contributes to organizational behavior and sustainability research by illustrating how employee mindsets shape sustainability implementation in agribusiness organizations.